Corporate Tournaments - Bognanno, Michael L. (Journal of Labor Economics, 2001)
This study examines aspects of pay and promotion in corporate hierarchies in the context of tournament theory. Evidence supports the tournament perspective in that most positions are filled through promotion and pay rises strongly with hierarchical level. Furthermore, the winner's prize in the CEO tournament increases with the number of competitors for the CEO position. Not all evidence is supportive: the square of the number of competitors is negatively associated with the CEO prize. Additionally, firms do not appear to maintain short-term promotion incentives, as lengthier time in position prior to a promotion reduces the pay increase from the promotion. Copyright 2001 by University of Chicago Press.